(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The study investigated the effect of Musanga cecropioides (MC) water-ethanol stem bark extract on blood glucose level in both hyperglycemic loaded glucose rats and streptozotocin (STZ)-induced diabetic rats, and evaluated its antioxidant capacity. The Wistar rats were induced diabetes after fasting. Oral Glucose Tolerance Test (OGTT) was conducted on normoglycemic rats, and anti-hyperglycemic test on diabetic rats; five groups with five rats each were constituted. Group 1: negative control was treated with vehicle; Group 2, Group 3, and Group 4 were treated with increasing water-ethanol extract (200, 300 and 400 mg/kg b.w); Group 5 was the positive control, treated with glibenclamide. The antioxidant capacity of the extract was also evaluated by measuring the Ferric Reducing Antioxidant Power, Total Phenolic Content, Total Flavonoid Content, and radical scavenging activity of water-ethanol stem bark extract. In OGTT the water-ethanol extract of MC, at the dose of 300 mg/kg, significantly lowered the Area under Curve (AUC) induced by glucose. In STZ diabetic rats, the extract significantly lowered the AUC of blood glucose, at all doses. Glibenclamide was more efficient in both OGTT and anti-hyperglycemic test. The MC extract presented relevant antioxidant activity with IC50 = 6.23 mg/mL. Both the Total Phenolic Content and the Total Flavonoid Content increased in a dose-dependent manner. The correlation of DPPH % free radical scavenged and Total Flavonoid Content was positive and statistically significant. MC water-ethanol extract possesses a good antioxidant potential, and could be helpful to lower hyperglycemic state associated with diabetes.